Is the 10-RM test ideal for evaluating trained and untrained individuals? - Lima,Fernando Max (2020)
ABSTRACT The objective was to evaluate whether the 10-RM test can be applied to both trained and untrained people in elbow flexor strengthening exercises. The sample consisted of 23 men aged between 18 and 30 years old, of which 11 were untrained (NT - control group), and 12 were resistance-trained (TR - trained group). The experiment started with a specific warm-up session followed by collections of myoelectric signals from the brachial biceps muscle, bilaterally, in Maximum Voluntary Isometric Contractions (MVIC), the 10-RM test for elbow flexion and the new MVIC, followed by deceleration. By analyzing each contraction separately contraction, a significant increase in RMS (Root Mean Square) was found by a normalized MVIC with regard to 1st contraction, starting from the 3rd repetition for the TR group. When comparing each contraction of the 10-RM test with the previous one, a significant reduction of MF (Median Frequency) between the 5th and the 6th repetition of the TR group was observed. It was concluded that the Test of 10 Maximum Repetitions should be reconsidered when performed for purposes of comparison between sides of the body. Also, when considering the probable fatigue caused by the successive movements, a better application of tests with 6 to 8 repetitions was suggested.